METHOD COMPARISON ANALYSIS SIMPLE ADDITIVE WEIGHTING (SAW) WITH WEIGHTED PRODUCT (WP) METHOD IN SUPPORTING THE DECISION TO ACCEPT NEW EMPLOYEES - Ramadhan, Idham; Zaky, Umar (University of Technology Yogyakarta, 2020)
Employee selection is the first step in a company or agency that aims to obtain qualified and competent human resources that will serve and do all the work on an instinct. The process of selection of prospective employees has two decisions that are accepted and rejected. When an agency or company is unable to determine the human resources that fit the required criteria, it will be very detrimental for an agency or company more than the number of prospective employees who register will be troublesome in terms of calculation and determining competent human resources and in accordance with the required criteria. In this case to minimize or solve the problem, the author designed and built a system to help the agencies, especially Gunung Jati Regional Hospital (RSD) in terms of the selection of new employee admissions. The development of this system by analyzing two methods, namely Simple Additive Weighting (SAW) method with Weighted Product (WP) method with the specified criteria. These two methods will be compared to get a good method and relevant to be applied in the selection of new employees at Gunung Jati Hospital so that the human resources received really match the needs of the agency. Analysis is carried out using the accuracy of each method by referring to the original data owned by the institution. The result of saw method conformity or percentage level is 99.959996% with an accuracy value of 84% and wp method of 99.959992% with an accuracy value of 76%. Thus the SAW method is the most relevant method to solve the problem of receiving new employees.